2022
DOI: 10.3390/soc12030078
|View full text |Cite
|
Sign up to set email alerts
|

“Mix of Races, Bad Uterus”: Obstetric Violence in the Experiences of Afro-Brazilian Migrants in Portugal

Abstract: In this article, I address the issues of obstetric violence and racism in the Portuguese setting of obstetric care. Based on data collected through interviews and participatory artistic creation, I analyze the perception of three Afro-Brazilian migrants about their perinatal experiences of obstetric care in the Portuguese public sector between 2013 and 2019. These women’s experiences have much in common with experiences of obstetric violence as narrated by Portuguese, non-racialized women. Despite this, certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Por añadidura, parece preciso subrayar que cuando se habla de violencia obstétrica no se hace referencia únicamente al parto ni a las/los profesionales que atienden directamente el embarazo, parto, alumbramiento, y puerperio sino también a todos los ámbitos y sectores que están implicados en dicho proceso, extendiéndose, por ejemplo, a los equipos de anestesia, pediatría, alumnado en práctica, residentes, personal administrativo, y de limpieza, puesto que se trata de un tipo de violencia estructural e institucional 27 . La violencia en el lugar de trabajo es un problema ocupacional importante también para los profesionales y tiene un impacto significativo en su bienestar físico y psicológico 28 . Por ello, en el momento en el que se comprende la complejidad y las numerosas implicaciones a nivel institucional y cultural de la violencia obstétrica, aparece la necesidad de asumir responsabilidades colectivas y formarse para mejorar la atención al nacimiento.…”
Section: Discussionunclassified
“…Por añadidura, parece preciso subrayar que cuando se habla de violencia obstétrica no se hace referencia únicamente al parto ni a las/los profesionales que atienden directamente el embarazo, parto, alumbramiento, y puerperio sino también a todos los ámbitos y sectores que están implicados en dicho proceso, extendiéndose, por ejemplo, a los equipos de anestesia, pediatría, alumnado en práctica, residentes, personal administrativo, y de limpieza, puesto que se trata de un tipo de violencia estructural e institucional 27 . La violencia en el lugar de trabajo es un problema ocupacional importante también para los profesionales y tiene un impacto significativo en su bienestar físico y psicológico 28 . Por ello, en el momento en el que se comprende la complejidad y las numerosas implicaciones a nivel institucional y cultural de la violencia obstétrica, aparece la necesidad de asumir responsabilidades colectivas y formarse para mejorar la atención al nacimiento.…”
Section: Discussionunclassified
“…Barata [18], in her very beautifully written and very interesting manuscript, addresses the issues of obstetric violence and racism in the Portuguese setting of obstetric care. Her research used qualitative methods and interviews with three Afro-Brazilian migrants about their perinatal experiences of obstetric care in the Portuguese public sector, between 2013 and 2019.…”
mentioning
confidence: 99%
“…For example, a qualitative study of Brazilian women living in Portugal found that most participants suffered discrimination for being Brazilians in their workplaces (de Diego-Cordero et al, 2022). In another example, a qualitative study interviewed Brazilian women in 2019 and again in 2021 about their experiences with obstetric care in Portugal (Barata, 2022). This study found that the intersection between race and class has added challenges to these Brazilian women's experiences in Portugal.…”
mentioning
confidence: 99%
“…Recent research in Aotearoa New Zealand reported that racism experiences are prevalent among some groups, including people from MELAA ethnicity, in which Brazilians are included (Simon-Kumar et al, 2022) (Barata, 2022;de Diego-Cordero et al, 2022). For example, a qualitative study of Brazilian women living in Portugal found that most participants suffered discrimination for being Brazilians in their workplaces (de Diego-Cordero et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation